MODERN CONCEPTS OF CHILDHOOD NON-HODGKIN LYMPHOMA - Adriana Sărsan; Constantin Arion (Amaltea Medical Publishing House, 2008)
The lymphomas are malignant transformations which can occur in any of the morphologically and functionally distinct subpopulations of lymphoid cells of the immune system and in any of the central or peripheral lymphoid organs, which accounts for the heterogeneity of morphologic, immunologic and clinical features observed in malignant lymphomas, as well as the incidence of generalized disease. Cytogenetic studies of lymphomas have provided some of the most exciting clues to the pathogenesis of these diseases. The application oh immunodiagnostic techniques to the diagnosis oh NHL has allowed more accurate identification of the lineage and thus the cell of origin of NHL. The most important advances in treatment of childhood NHL resulted from the recognition of the systemic nature of these diseases and their potential for rapid dissemination even from apparently localized sites of disease. Keywords: Childhood Non-Hodgkin Lymphoma; correlation of histopathologic subgroup, immunophenotype, clinical features and cytogenetics.